1994
DOI: 10.1037/0022-006x.62.4.729
|View full text |Cite
|
Sign up to set email alerts
|

Toward the incorporation of costs, cost-effectiveness analysis, and cost-benefit analysis into clinical research.

Abstract: Most research in clinical psychology and related disciplines does not measure, report, or analyze costs, cost-effectiveness, or cost-benefit analysis. Reasons for this are discussed. It may be thought, for example, that costs are trivial to measure. Data are presented to show that the values of resources consumed in treatment (i.e., costs) actually can be quite complex to assess accurately and completely. Research findings are assembled to show that costs, as experienced by clients, may be beneficial to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 19 publications
0
83
0
1
Order By: Relevance
“…In my experience, it is criticized as secondary in importance, mundane to conduct, or too site-or therapist-specific to be of use to the field. Similar arguments were made decades ago against the desirability of conducting research on the cost effectiveness of different therapeutic technologies (e.g., Strupp, 1981) Research on less costly and more effective ways to deliver therapy is what we need, so that we can use evidence-based delivery systems to provide evidence-based services to the most people for the least necessary expenditure of resources per person (Yates, 1980(Yates, , 1994. This sort of research is only beginning to be conducted in a thorough, systematic manner that includes careful measurement of costs, and effectiveness, from multiple perspectives (cf.…”
Section: Fundingmentioning
confidence: 99%
“…In my experience, it is criticized as secondary in importance, mundane to conduct, or too site-or therapist-specific to be of use to the field. Similar arguments were made decades ago against the desirability of conducting research on the cost effectiveness of different therapeutic technologies (e.g., Strupp, 1981) Research on less costly and more effective ways to deliver therapy is what we need, so that we can use evidence-based delivery systems to provide evidence-based services to the most people for the least necessary expenditure of resources per person (Yates, 1980(Yates, , 1994. This sort of research is only beginning to be conducted in a thorough, systematic manner that includes careful measurement of costs, and effectiveness, from multiple perspectives (cf.…”
Section: Fundingmentioning
confidence: 99%
“…18 Research on cost-effectiveness of obesity treatment in adults 19 -21 has shown that less intensive treatments may not differ significantly in outcome from more intensive treatments, thus improving the costeffectiveness of these treatments. Similar efficacy for individual and group treatments in children 17 suggests that group treatments would be more cost-effective than individual treatments in youth.…”
Section: Introductionmentioning
confidence: 99%
“…And finally, we looked at QALY(G)s over 1 year, rather than over a participant's lifetime, as is the typical method for assessing QALYs. Despite these limitations, incorporating QALYs into treatment-outcome research for SAD moves us one step closer to completing the research agenda argued for by Yates (1994): the assessment of both costs and outcomes to allow for more complete theoretical and empirical models of mental health treatment.…”
Section: Discussionmentioning
confidence: 99%
“…That is, measures such as the Beck Depression Inventory, 2nd Edition (BDI-II; Beck et al, 1996) can be used only to compare the effectiveness of interventions for depression. In a climate of potentially scarce resources, effective interventions must also be cost-effective (Yates, 1994). A more generic outcome is needed to compare the cost-effectiveness of depression-related interventions against the effectiveness of interventions for other disorders (Pyne et al, 2003).…”
Section: Seasonal Affective Disorder and Quality Adjusted Life Yearsmentioning
confidence: 99%